(untitled) (Journal of Atomic and Molecular Sciences, 2015)
Based on the 1²A" global three-dimensional adiabatic potential energy surface [Boggio-Pasqua et al., Phys Chem. Chem. Phys 2:1693-2000], a theoretical study of the stereodynamics of the reaction C(^3P)+CH(X^2Π) (v=0; j=0-6) has been performed using the quasi-classical trajectories(QCT) method. The cross sections are caculated. The differential cross sections (DCSs) and the distributions of P(θ_r), P(φ_r) are pensented in detail at the selected collision energy of 0.3 eV. The product rotational alignment parameter are also obtained as a function of the regent rotational quantum number. The results show that the reagent rotational excitation plays an important role in the title reaction.